The Impact of Influencer Marketing on Consumers’ Intentions Toward Beauty Brands After the Covid-19 Pandemic - Khurshid, Sakar; Ayoub, Doaa; Kortam, Wael (The Arab Journal of Administration, 2024)
Influencer marketing is extremely used nowadays by brands all over the world. Influencers give brands an edge to achieve their goals and sales. As they impact consumers’ intentions to buy beauty products, especially after the Covid-19 pandemic. Covid-19 made many companies reach to influencers to market their products as it was easier and faster. The main purpose of this paper is to identify the impact of influencer marketing on consumers’ intentions toward beauty brands after the Covid-19 pandemic. Understanding whether the beauty influencer’s credibility, attractiveness, expertise, and product match-up, impact consumers’ intentions. The paper set up the four factors of influencer marketing (credibility, attractiveness, expertise, and product match-up) as independent variables, and the dependent variable is consumers’ intentions. The research data of this paper based on quantitative research through using online survey. The sample comprised 202 target consumer who lives in Iraq and uses social media platforms to buy beauty products. The results show that there is a crucial relationship between influencer marketing and its dimensions (credibility, attractiveness, expertise, and product match-up) and consumers’ intentions. However, not all influencer marketing dimensions are influencing the consumers’ intentions.